Synthesis and photorelease studies from model quinolone conjugates - Domingues, B. B. (2013)
We present the synthesis and the photolytic release at longer wavelengths of phenylalanine, acting as a model amino acid, from conjugates bearing a methoxylated quinolone 2a,b. The photolytic study was carried out by irradiation at 300, 350 and 419 nm in a methanol/HEPES buffer solution (80:20). Monitoring of the photolysis of 2a,b and consequent release of N-benzyloxycarbonylphenylalanine was carried out by HPLC-UV detection and kinetic data was obtained.